GENDER EQUALITY STUDIES: THE DOMESTIC POLITICAL INFLUENCE ON JAPAN’S OFFICIAL DEVELOPMENT ASSISTANCE (ODA) POLICY - Zahidiyah Ela Tursina; Sartika Soesilowati (International Conference on Social and Islamic Studies, 2021)
Japan is a country that has concern to gender equality, so that, Japan’s Official Development Assistance (ODA) policy has gender equality values. This paper use domestic political and foreign aid concept and also the power of idea on state policy concept. And then,based on research analysis, it can concluded that domestic political in the form, gender equality idea can influence Japan’s ODA policy. Gender equality idea can internalize into Japan’s foreign aid policy, so that, it can be applied into recipients countries. But, when Japan distribute ODA foreign aid  based on equality gender values to recipient countries, Japan get some challenges.The challenges are opinion public factor to  Prime Minister of Japan, Shinzo Abe and also factor of conservative cultural norm and patriarchy in recipients countries which is developing country.